"Decolonization in the World of Christian NGOs" : A Theological Response - Bray, Charlotte (Christian Relief, Development, and Advocacy: The Journal of the Accord Network, 2024)
On January 17, 2024, the Accord Research Alliance Faculty Group organized a webinar to provide a space for discussion on the Christian Relief, Development, and Advocacy (CRDA) journal’s special issue on decolonization published a few months before in November 2023. The webinar was moderated by Nina Kurlberg, one of two co-editors of the special issue, and started with remarks by two main discussants. This second response is written by Charlotte Bray, who is currently studying anti-racism and power in international development from a Catholic theological perspective at the Lincoln Theological Institute at Manchester University. Believing that our theologies are central to our self-understandings and our actions, for both good and ill, Bray argues that historical Christianity bears much responsibility for the way the Global North skewed power toward themselves, a legacy for which we must account. Working from the perspective of Catholic Social Teaching, a rich resource for putting our theology on a more constructive path, she argues that Christians must take advantage of opportunities to make amends and work toward reconciliation in a newly structured anti-racist, decolonized world. The full recording of the webinar is found at https://vimeo.com/903813593?share=copy, and further online discussion on the topic can be accessed at https://groups.google.com/g/ara-faculty-group-forum. The special issue of the journal with all the articles is located at https://crdajournal.org/index.php/crda/issue/view/69.